O Boticário: a trajetória do João Ladislau de Figueiredo e Mello (Bahia, 1772-1856) - Santos, José Pedro Soares (2023)
João Ladislau de Figueiredo e Mello, during his lifetime, played an important role in the intricacies of the political, economic and intellectual spheres of the Captaincy and, later, of the Province of Bahia. However, historiography shows a lack of comprehensive studies and significant gaps in relation to his trajectory. This work intends to explore the political and intellectual journey of João Ladislau de Figueiredo e Mello, placing him in the context of the political changes that shook Bahia during the final decades of the 18th century, culminating in the consolidation of the Brazilian Imperial Order. The character was active in the Portuguese Empire, from the end of the 18th century, the first half of the 19th century and with the purpose of establishing a transformation in the structures established and influenced by the enlightened reform movement in Portugal and in tune with his own motivations and interests. of the Portuguese Crown. This study intends to explore the political and intellectual journey of this individual, allowing us to obtain a renewed vision of the social and economic dynamics of the Portuguese Empire, especially in the context of nineteenthcentury Bahia.